A comprehensive overview on intelligent mechanical systems and its applications. (2021) - David, Shibin; Anand, R.S.; Sheikh, Sarah; Jebapriya, S.; Andrew, J.; Basil Xavier, S.
Abstract: The serenity of the materials can be reflected from the load applied over them to extract its strength and scope. Perhaps the tender nature of the materials and its behavior such as ductility, hardness, impact resistance, the measurement of such behavior remains complex. To replace the efforts of conventional machine elements and man-power over the attributes of the materials deployed, artificial intelligence plays a significant role. It replaces the intelligence of human with the intelligence exhibited by the machines. Many artificial intelligence algorithms can learn from data, they can improve themselves by learning new heuristics or they can write new algorithms themselves. Nowadays, artificial intelligence is being used in most of the equipments we use, it includes from search engines to recent autonomous cars. Intelligent manufacturing will enable the users to fabricate machines as well as machine elements with new functionalities and applications. In this article, the impact of intelligent machines employed in various domains, its technical features are discussed with their applications.